METHODS OF ASSESSING THE EFFICIENCY OF PROFESSIONAL TRAINING OF FUTURE QUALIFIED WORKERS OF MECHANICAL BUILDING, AGRICULTURAL INDUSTRY AND THE FIELD OF SERVICES INCONDITIONS OF MIXED LEARNING (Innovative professional education, 2024)
Aspects of the effectiveness of distance education, their research and ways of improvement are considered. Proposed indicators for assessing performance in thecontext of each aspect. The indicators that measure the effectiveness of distance education are described, taking into account the social responsibility of educationalinstitutions. Approaches to measuring the economic efficiency of education are given. Special attention is paid to the factors on which it depends and the proposed ways of increasing it.
Keywords: distance learning, blended learning, educational efficiency, economic efficiency of distance learning